Scientific literature landscape analysis of researches on oxidative stress in intervertebral disc degeneration in web of science - Cheng, Yunzhong; Yang, Honghao; Hai, Yong; Zhou, Lijin (Frontiers in Molecular Biosciences, 2022)
Oxidative stress plays a significant role in the development of disc degeneration and has attracted widespread attention since it was first researched in 2007. Our study aims to analyze the scientific output of oxidative stress in intervertebral disc degeneration (IDD) and drive future research into new publications. Publications focused on this topic were retrieved from the SCI-EXPANDED (SCI-E) of the Web of Science (WOS) core collection database and were screened according to the inclusion criteria. Bibliometric website, VOSviewer, and Citespace software were used to evaluate and visualize the results, including annual publications, citations, authors, organizations, countries, research directions, funds, and journals. As of February 16, 2022, a total of 289 original articles and reviews were included, and the overall trend of the number of publications rapidly increased. China and the USA were the leading countries for research production in worldwide. The retrieved 289 publications received 5979 citations, with an average of 20.67 citations and an H-index of 40. The most high-yield author, organization, country, research direction, fund, and journal were Wang K from Tongji Medical College, Huazhong University of Science Technology, China, Cell Biology, National Natural Science Foundation of China, Oxidative Medicine and Cellular Longevity, respectively. The majority of most common keywords were related to the mechanisms and regulatory networks of oxidative stress. Furthermore, with accumulating evidence that demonstrates the role of oxidative stress in IDD, “mitochondria” and “senescence” are becoming the new research focus that should be paid more attention to.